Combiner to Reduce the Time of Processing in Trend Analysis Using Hadoop's MapReduce Framework - Pinto, Vivek Francis (2017 2nd International Conference on Computational Systems and Information Technology for Sustainable Solution (CSITSS), 2017)
Trend means to be one of the words, subjects, or names that is being mentioned most often on a social media website or a news website at a particular time or for a duration of time. It also means that a particular behaviour or method change done or being undertaken or followed by people may be individual or as a group. Taking the advantage of the fast phased processing technology helps in analysing the trends in the current times. Apache Hadoop frame work provides Mapper and Reducer which helps to mine the large amount of data and to help the business to plan their marketing tactics based on the trend. Further, using concept of Combiner, which is an important feature of Hadoop framework, immensely reduces the processing time and gives the mining results in less time compared to the one without Combiner, which reduces the entire processing time in bigger difference as the file size increases. The main motivation behind this research is that need of improved processing time of larger files, utilizing the Hadoop's available features.